Effectiveness of NEPIL (Pain, Elimination, Position, Infusion and Environment) Nursing Rounding Implementation on Patient Satisfaction Level: Literature Review : - Ni Wayan Wirayanti Ni Wayan; Grace Solely Houghty (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: This study is conducted to determine the effectiveness of Nursing Rounding Implementation on the level of patient satisfaction. Nursing Rounding can also reduce the incidence of falls, plebitis rates and bell ringing if done correctly. Objective: Nursing Rounding has an impact on patient satisfaction. Nursing Rounding can also reduce the incidence of falls, plebhitis rates and bell ringing if done properly. Method: literature review uses journals identified from Pubmed, EBSCO, crossref, Pro Quest and Google Scholar. Result: The results of the 17 journals taken from 2018-2023 state that Nursing Rounding can increase patient satisfaction rates, improve patient safety quality, reduce the incidence of plebhitis, reduce the number of bell calls and reduce the incidence of falls. Conclusion: Nursing Rounding is a systematic process used by professional health care providers to anticipate and address the fundamental needs of patients, especially in the treatment room. Nursing Rounding uses NEPIL systematics, namely pain, elimination, position, infusion, Possesion, and patient environment to improve patient satisfaction.